2011
DOI: 10.1186/1471-2458-11-478
|View full text |Cite
|
Sign up to set email alerts
|

Applying the revised Chinese Job Content Questionnaire to assess psychosocial work conditions among Taiwan's hospital workers

Abstract: BackgroundFor hospital accreditation and health promotion reasons, we examined whether the 22-item Job Content Questionnaire (JCQ) could be applied to evaluate job strain of individual hospital employees and to determine the number of factors extracted from JCQ. Additionally, we developed an Excel module of self-evaluation diagnostic system for consultation with experts.MethodsTo develop an Excel-based self-evaluation diagnostic system for consultation to experts to make job strain assessment easier and quicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The 2 first sections have dealt with data of the JS and the 2 following with data of the MQL. In this study, the proportion of subjects having the JS (59.3%) is much higher than those of the French general population (23%) [20] and those of nurses studied in Sweden, Canada, or China [29][30][31]. This high rate can be explained by the hospital work environment [32].…”
Section: Discussionmentioning
confidence: 84%
“…The 2 first sections have dealt with data of the JS and the 2 following with data of the MQL. In this study, the proportion of subjects having the JS (59.3%) is much higher than those of the French general population (23%) [20] and those of nurses studied in Sweden, Canada, or China [29][30][31]. This high rate can be explained by the hospital work environment [32].…”
Section: Discussionmentioning
confidence: 84%
“…The studies that tested JCQ reliability and validity (mostly, decision latitude, psychological job demands, supervisor support, and co-worker support scales) have generally found acceptable psychometric characteristics and substantial comparability of the JCQ scales across populations (Choi et al, 2009;Fransson et al, 2012;Jabali et al, 2013), despite some exceptions, as is the case of the psychological job demands scale, that shows low internal consistency in some studies (Kawakami et al, 1995;Phakthongsuk, & Apakupakul, 2008). The studies also found different results in the decision latitude scale that can challenge the theoretical framework: some identify two factors in that scale -skill discretion and decision authority (Chien et al, 2011;Karasek et al, 1998;Smith, Tisak, Hahn, & Schmieder, 1997) -, and others only one factor (Niedhammer et al, 2006;Pelfrene et al, 2001;Phakthongsuk, & Apakupakul, 2008;Zotnierczyk-Zreda, & Bedyriska, 2014).…”
Section: Assessing Stress At Work: the Portuguese Version Of The Job mentioning
confidence: 99%
“…The JCQ has been translated in 23 different languages (http://www.jcqcenter.org) and has been widely used worldwide in different socioeconomic strata and cultures, including Mexico [Juárez‐Garcia, ; de Araujo and Karasek, ; Maizura et al, ; Chien et al, ; Gómez‐Ortiz, ]. Job strain has been identified as a risk factor for a number of health outcomes, including cardiovascular disease [Belkic et al, ], psychological disorders [Stansfeld and Candy, ; Bonde, ], and musculoskeletal disorders [Mantyniemi et al, ].…”
Section: Introductionmentioning
confidence: 99%